Transformasi industri dengan teknologi 4.0: Revolusi digital di era modern - Sa'diyah, Halimatus (Maliki Interdisciplinary Journal, 2024)
The world of manufacturing industry is experiencing a major transformation due to the industrial revolution 4.0, combining digital, physical and biological technology to increase efficiency, productivity and connectivity. Positive impacts include increased productivity, reduced costs, and the creation of innovative products. However, this transformation also presents challenges such as company adaptation, changes in worker mindsets and skills, information security, and the digital divide. The government, business sector, and society need to collaborate to improve education and digital literacy, expand internet access, create appropriate regulations, and use technology responsibly to maximize the benefits and minimize the negative impacts. Indonesia needs to prepare itself by strengthening new literacy, including writing, reading, communication, critical thinking, collaboration, creative and innovative skills. The world of education must integrate old literacy, new literacy and science to produce graduates who are competent in this digital era strictly in abstract format. The integration of digital, physical and biological technology indicates that the world of manufacturing industry is entering the era of industrial revolution 4.0. This article discusses digital transformation and its impact on the industry. Technologies such as the Internet of Things (IoT), Artificial Intelligence (AI), Big Data, and Cloud Computing are the main pillars of this era, enabling equipment automation, big data analysis, and more efficient.